Disonansi Kognitif Dalam Gerakan Sosial Pemboikotan Produk Food And Beverage Yang Diasosiasikan Dengan Dukungan Terhadap Israel - Radita Gora Tayibnapis; Marwa Ulfa; Farida Hariyati (JOM, 2026)
The boycott movement against multinational food and beverage (F&B) brands, particularly McDonald's, KFC, and Starbucks, has emerged as a significant form of consumer activism in response to the Israel–Palestine conflict. This study aims to examine the influence of media exposure and social boycott movements on public perceptions and consumer boycott behavior through the perspective of Cognitive Dissonance Theory. The research employed a quantitative explanatory design using a survey method with structured questionnaires administered to respondents. Data were analyzed using descriptive statistics and factor analysis to identify the dominant determinants influencing public participation in the boycott movement. The findings indicate that media exposure and social boycott campaigns significantly shape public perceptions, which subsequently encourage changes in consumer behavior toward boycott participation. Factor analysis extracted five principal factors that collectively explained 68.066% of the total variance, indicating that the proposed model adequately represents the dimensions of boycott behavior. The most influential indicator was respondents' participation in boycott actions based on media information (loading = 0.814), followed by actively seeking updated information about products perceived to support Israel (loading = 0.804). These findings demonstrate that persuasive communication, digital information dissemination, and collective participation are the primary determinants of consumer boycott behavior. The study confirms the relevance of Cognitive Dissonance Theory in explaining how inconsistencies between consumers' moral values and purchasing behavior encourage behavioral change through ethical consumption. This research contributes to the literature on consumer behavior, digital activism, and ethical consumption by highlighting the strategic role of social media in shaping public perceptions and mobilizing collective action in humanitarian issues.